Perceived—and not manipulated—self-control depletion predicts students' achievement outcomes in foreign language assessments. Issue 4 (20th April 2020) - Lindner, Christoph; Retelsdorf, Jan
Abstract: In the present study we investigated which role manipulated (i.e., experimentally induced) and perceived (i.e., self-reported) self-control depletion plays in students' ( N  = 176 seventh graders) achievement-related experiences and behaviour during a test of English as a foreign language, while controlling for trait self-control. Our successful experimental manipulation of self-control depletion revealed that there were no effects on any of the students' outcome variables. However, students who reported high self-control depletion immediately after the experimental manipulation were less motivated to work on the subsequent test, reported more distracting thoughts, showed lower performance, and felt more depleted at the end of the test session. Trait self-control turned out to be a protective and supportive factor for most of our outcome variables. Our results provide evidence that the perceived and not the manipulated level of self-control depletion is a predictor of achievement-related behaviour in tests on English as a foreign language.